Antioxidant Properties of Honey: Mechanisms and Clinical Applications - Yunus, Mohammed (Free Radicals and Antioxidants)
Honey is a natural antioxidant source that has gained popularity in recent years due to its possible health benefits. Its antioxidant properties derive from its unique composition of phytochemicals and other compounds, which work in line to neutralise free radicals and upregulate antioxidant enzymes. This review summarises the composition and antioxidant mechanisms of honey, as well as the in vitro, animal, and human evidence for its antioxidant activity. In addition, potential clinical applications of honey's antioxidant properties are discussed, such as its use in preventing chronic diseases, promoting wound healing and skin health, and possibly as an adjunct to cancer therapy. Finally, honey's impact on antioxidant activity as well as its safety and quality are discussed.
Keywords: Honey; Antioxidants; Phytochemicals; Oxidative Stress; Chronic Diseases; Wound Healing; Skin Health; Cancer Therapy; Safety; Quality